SISTEM PEMBERIAN KODE PADA DATA - Amelia Setiawan (Bina Ekonomi, 2003)
Coding systems is the assignment of symbols such as letters and numbers to provide specific identification of an object. Effective code provide unique and concise information of an object. In many cases, coding is used for making classification schemes that is useful for accounting systems. A coding systems consist of character set that is symbols that are used to define something. Accountants commonly use coding systems when they design chart of accounts.